2017
DOI: 10.1002/bab.1515
|View full text |Cite
|
Sign up to set email alerts
|

A review on the important aspects of lipase immobilization on nanomaterials

Abstract: Lipase is one of the most widely used enzymes and plays an important role in biotechnological and industrial processes including food, paper, and oleochemical industries, as well as in pharmaceutical applications. However, its aqueous solubility and instability make its application relatively difficult and expensive. The immobilization technique is often used to improve lipase performance, and the strategy has turned out to be a promising method. Immobilized lipase on nanomaterials (NMs) has shown superiority … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
61
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(68 citation statements)
references
References 111 publications
1
61
1
1
Order By: Relevance
“…Compared to free lipases, their immobilized counterparts can be obtained through physical adsorption, physical entrapment, covalent bonding, and chemical crosslinking, with improved stability against heat and pH, easy recovery and reusability, and suitability for continuous processes (Facin, Melchiors, ValéRio, Oliveira, & Oliveira, 2019;Mateo, Palomo, Fernandez-Lorente, Guisan, & Fernandez-Lafuente, 2007). For physical immobilization, lipases can be immobilized onto the supports through weak interactions including van der Waals forces, hydrogen bonds, and hydrophobic interactions, or can be confined inside the support matrix, whereas chemical immobilization generally involves the formation of covalent bonds between the amino groups of lipases and the functional groups of the carriers (Facin et al, 2019;Shuai, Das, Naghdi, Brar, & Verma, 2017).…”
Section: Lipase Immobilization Techniquementioning
confidence: 99%
“…Compared to free lipases, their immobilized counterparts can be obtained through physical adsorption, physical entrapment, covalent bonding, and chemical crosslinking, with improved stability against heat and pH, easy recovery and reusability, and suitability for continuous processes (Facin, Melchiors, ValéRio, Oliveira, & Oliveira, 2019;Mateo, Palomo, Fernandez-Lorente, Guisan, & Fernandez-Lafuente, 2007). For physical immobilization, lipases can be immobilized onto the supports through weak interactions including van der Waals forces, hydrogen bonds, and hydrophobic interactions, or can be confined inside the support matrix, whereas chemical immobilization generally involves the formation of covalent bonds between the amino groups of lipases and the functional groups of the carriers (Facin et al, 2019;Shuai, Das, Naghdi, Brar, & Verma, 2017).…”
Section: Lipase Immobilization Techniquementioning
confidence: 99%
“…In the last years, magnetic metal oxide nanoparticles have had considerable progress as inorganic carriers for enzyme immobilization since a selective magnetic separation from the reaction mixture makes them useful for a smart immobilization . In this line, nanoparticles of metal ferrite have been continually evaluated in recent years for its use in biocatalysis …”
Section: Introductionmentioning
confidence: 99%
“…The bilayer membrane component of BMs contains many amino groups, which can be combined with biological molecules that include enzymes, antibodies, and antitumor medicines . Many in vitro results have demonstrated that BMs have many advantages over artificial iron oxide nanoparticles, particularly when the nanoparticles are used for biological applications .…”
Section: Introductionmentioning
confidence: 99%